Experimental Study on Production of Biogas from Kitchen Waste (International Journal of Innovative Research in Engineering & Management, 2023)
In our institute we have four hostels and  all having their own individual mess, where daily a large  amount of kitchen waste is obtained which can be utilized  for better purposes. Biogas production requires  Anaerobic digestion. Project was to create an Organic  Processing Facility to create biogas which will be more  cost effective, eco-friendly, cut down on land fill waste,  generate a high-quality renewable fuel, and reduce carbon  dioxide & methane emissions. Overall, by creating a  biogas reactor on campus in the backyard of our hostels  will be beneficial. Kitchen (food waste) was collected  from different hostels of PACE IT & S Mess as feed  stock for our reactor which works as an aerobic digester  system to produce biogas energy. The anaerobic digestion  of kitchen waste produces biogas, a valuable energy  resource Anaerobic digestion is a microbial process for  production of biogas, which consist of Primarily methane  (CH4) & carbon dioxide (CO2). Biogas can be used as  energy source and also for numerous purposes. But any  possible applications require knowledge & information  about the composition and quantity of constituents in the  biogas produced. The continuously-fed digester requires  addition of sodium hydroxide (NaOH) to maintain the  alkalinity and pH to 7. For this reactor we have prepared  our Inoculum than we installed batch reactors, to which  inoculum of previous cow dung slurry along with the  kitchen waste was added to develop our own Inoculum. A  combination of these mixed inoculum was used for  biogas production at 37°C in laboratory (small scale)  reactor (20L capacity) In our study, the production of  biogas and methane is done from the starch-rich and  sugary material and is determined at laboratory scale  using the simple digesters.
Keywords: Anerobic Digestion; BOD; Biogas; Kitchen Waste; Digester